Examining Pre-school Teachers’ and Parents’ Views on Counseling and Guidance Services in Pre-school Education - Gulsen Buyuksahin Cevik (Institute of Advanced Engineering and Science, 2017)
Current study aims to reveal the problems that pre-school teachers and parents face, in relation to guidance and counseling services, at schools without psychological counselors. The purpose of including pre-school teachers and parents in the current study was to find out both whether they considered the guidance and counseling services a need and whether their methods of intervention against the problems that they face were functional. The current research was designed with interview technique as a qualitative study method. Research data were collected through a semi-structured interview form developed by the researcher. The researcher met the participants individually and asked the questions on the interview form for the current research. The responses that the participants provided were recorded and later transferred onto computer environment. The study group, formed based on voluntary participation, included total 30 participants with 15 pre-school teachers and 15 parents of pre-school children. Pre-school teacher participants 10 females and 5 males, worked for five different preschools in Adiyaman. Total 15 parents in the study group included nine females and six males. An examination of pre-school teachers’ responses based on the current study findings indicated that majority of the teachers did not prepare an annual counseling and guidance plan. Another finding of the current study was that children of most parents and teachers experience adjustment problems in pre-school. Another finding of the current research is about children’s individual problems. Main individual problems that parents experienced with their children included self-care and social development.